2000
DOI: 10.1021/ol000251c
|View full text |Cite
|
Sign up to set email alerts
|

Meso Aryl Heptaphyrins:  The First 30π Aromatic Expanded Porphyrins with an Inverted Structure

Abstract: [reaction: see text] Synthesis of new meso aryl 30pi heptaphyrins 2, 3, and 4 is achieved. Spectroscopic studies reveal that 2, 3, and 4 are aromatic and possess an inverted structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
4

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
1
38
0
4
Order By: Relevance
“…[107] As shown previously in Scheme 24, reaction of 82 a or 82 b with either 43 a or 43 c produced macrocycles 84 a-d, respectively, in yields ranging from 15 to 20 %. Curiously, despite the moderate yields obtained, the report does not comment on the formation of other macrocycles that might be expected; for example, products derived from the self-coupling of the respective precursors (see, however, Sections 5.3 and 7.5).…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…[107] As shown previously in Scheme 24, reaction of 82 a or 82 b with either 43 a or 43 c produced macrocycles 84 a-d, respectively, in yields ranging from 15 to 20 %. Curiously, despite the moderate yields obtained, the report does not comment on the formation of other macrocycles that might be expected; for example, products derived from the self-coupling of the respective precursors (see, however, Sections 5.3 and 7.5).…”
Section: Methodssupporting
confidence: 52%
“…For example, as reported in the Supporting Information of the paper, [107] the CH protons of the inverted selenophene subunit in 84 d were found to resonate as a singlet at d = À1.62 ppm, while two singlets were seen at d = 0.02 and À0.47 ppm which are ascribed to the two different NH signals. Also in accord with the proposed aromatic character, signals ascribed to the "outer" b-CH protons of 84 d were found between d = 9.07 and 10.17 ppm.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…The expected rubyrins were not formed when the meso substituents were phenyl or tolyl in both the precursors, indicating the necessity of the bulkier group in at least one of the precursors, while keeping the acid concentration the same and changing the mesityl substituents for a p-methoxy substituent in the terthiophene diol resulted in the formation of [ It is well known that tripyrranes and tetrapyrranes undergo acidolysis in the presence of acid and that the extent of acidolysis depends on the concentration of acid in the reaction mixture. [9,11] Acidolysis of 11 and 12 has already been reported. [9] It has been reported that in the reaction of tripyrranes 11 or 12, with 0.3 equiv.…”
Section: Synthesesmentioning
confidence: 99%
“…In these syntheses an efficient approach involving [3 + 3] acid-catalyzed condensations of terthiophene diols [9] 7-10 and tripyrranes 11-14 was applied (Scheme 1). Mixtures of the appropriate diol and tripyrrane were stirred in the presence of p-toluenesulfonic acid (PTSA) in dry CH 2 Cl 2 in the dark at room temperature.…”
Section: Synthesesmentioning
confidence: 99%